Comment on "Football-specific fitness testing: adding value or confirming the evidence?" - Carling, C.; Collins, D. (Journal of Sports Sciences, 2014)
The recent point-counter-point exchange arising from the article by Mendez-Villanueva and Buchheit (2013) (Football-specific fitness testing: Adding value or confirming the evidence? Journal of Sports Sciences, 31, 1503-1508) has generated an interesting debate on the real-world utility of fitness testing in professional association football (soccer). In the present authors` opinion, this exchange could also have been placed more in the context of the physical testing and subsequent benchmark profiling of the youth player within elite academy talent identification and development processes. This point is further strengthened by the current media debate at the time of writing on the development of elite youth football players in England and the Elite Player Performance Plan or EPPP (The Premier League. (2011). Elite Player Performance Plan. London: Author) published by the English Premier League as part of a vision for the future development of youth football in the League and throughout the English professional game. The EPPP recommends the implementation of a national database to enable comparison of Academy player performances against national physical testing "benchmark" profiles. In continuing the above debate, this letter questions the real-world utility and potential pitfalls of nationwide athletic benchmark profiling programmes for elite youth football.